Species richness and composition differ in response to landscape and biogeography: data from Stockholm (outer) Archipelago (Baltic Sea), summer months 2009-2010. - Elsa Aggemyr; Alistair G Auffret; Love Jädergård; Sara Cousins (Stockholm University, 2017)
Data for "Species richness and composition differ in response to landscape and biogeography" by Aggemyr, Auffret, Jädergård and Cousins.
The plant survey was conducted during the summers of 2009 and 2010 in the outher archipleago of Stockholm, Baltic Sea. A total of 112 islands are included in the data.

The data includes:"2009-2010Baltic_explanatoryVariables.csv" - explanatory variables from 112 islands: island area, height, group, distance to mainland, shannon diversity index for habitat heterogeneity, structural connectivity for buffer radii 100, 1000, and 4000 metres, and also geographical position in WGS84.
"2009-2010Baltic_speciesComposition.csv" - a matrix of species presence/absence on each island.
"2009-2010Baltic_speciesRichness.csv" - number of species on each island.
"2009-2010Baltic_lifeFormClassification.csv" - species classified into four different life forms.
"2009-2010Baltic_map.jpg" - a map illustrating Stockholm archipelago, Baltic Sea, and the surveyed islands.
"2009-2010Baltic_readMe.txt" - a more detailed file description.

Please feel free to get in touch!
Keywords: 60302 Biogeography and Phylogeography; Plant Biology; Other Biological Topics; Annan biologi